2011
DOI: 10.1038/modpathol.2010.196
|View full text |Cite
|
Sign up to set email alerts
|

Specificity of brachyury in the distinction of chordoma from clear cell renal cell carcinoma and germ cell tumors: a study of 305 cases

Abstract: Brachyury is recognized as a specific marker for notochord-derived tissues and neoplasms, and has become a defining immunohistochemical feature of chordoma. The main differential diagnostic consideration for chordoma is chondrosarcoma, which is known to lack brachyury expression. However, within the spectrum of genitourinary neoplasia, metastatic germ cell tumors and clear cell renal cell carcinoma may also be close morphological mimics of chordoma, particularly given the increasing prevalence of small tissue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 22 publications
1
34
0
Order By: Relevance
“…14 Nuclear expression of brachyury is a consistent feature of chordoma ( Figure 3), which is a helpful diagnostic immunohistochemical finding to distinguish this tumor type from potential histologic mimics, including chondrosarcoma, metastatic carcinoma, and myoepithelial tumors. [14][15][16][17] No other consistently brachyury-positive tumor types have been identified. Of note, a subset of chordomas show copy number gains at the T locus.…”
Section: Lineage-restricted Transcription Factorsmentioning
confidence: 99%
“…14 Nuclear expression of brachyury is a consistent feature of chordoma ( Figure 3), which is a helpful diagnostic immunohistochemical finding to distinguish this tumor type from potential histologic mimics, including chondrosarcoma, metastatic carcinoma, and myoepithelial tumors. [14][15][16][17] No other consistently brachyury-positive tumor types have been identified. Of note, a subset of chordomas show copy number gains at the T locus.…”
Section: Lineage-restricted Transcription Factorsmentioning
confidence: 99%
“…A few cases of conventional chordomas and chondroid chordomas demonstrated the absence of brachyury staining, which was presumed to be due to inadequate fixation of tissue and poor antibody penetration [30,42] . Brachyury expression has reportedly not been observed in chondrosarcoma, liposarcoma, myoepithelial tumors, germ cell tumors, or clear cell renal cell carcinoma [35,38,42,43] . However, Miettinen et al immunohistochemically evaluated 5,229 different tumors for nuclear brachyury expression (rabbit monoclonal antibody; 1:2000 antibody dilution) and had shown that brachyury expression is prevalent in embryonal carcinoma, seminoma, and small cell carcinoma of the lung, but very rarely in common carcinomas such as ductal carcinomas of the breast or adenocarcinomas of the prostate, sarcomas, and melanoma [39] .…”
Section: Discussionmentioning
confidence: 99%
“…Patients with no gross RD after primary cytoreduction had a median survival of 106 months, and it was proposed that the resection of all visible disease significantly improved survival and should be the primary surgical goal of CS [9] . The impact of radical abdominal CS procedures (splenectomy, liver resection, extensive peritonectomy) on RD and the associated survival outcome of 194 patients with stage IIIC epithelial ovarian cancer receiving adjuvant platinum-based chemotherapy (including paclitaxel or cyclophosphamide) for six to eight cycles after undergoing primary surgery were analyzed [43] . A total of 131 (67.5%) patients were found to have RD ≤1 cm in maximal diameter.…”
Section: Impact Of Extensive Abdominal Surgery On Survivalmentioning
confidence: 99%
See 1 more Smart Citation
“…The neoplastic cells are embedded in extensive myxoid stroma that lacks the 'grungy' calcification of PMT. Immunohistochemistry is particularly useful in making this diagnosis with chordomas being positive for S-100, cytokeratin, EMA, and brachyury [13].…”
Section: Discussionmentioning
confidence: 99%